The Influence of Workload and Work Motivation on the Work Productivity of Members of the Criminal Research Unit (Satreskrim) of the Karawang Police - Neng Lisnasari Yulianti; RM Juddy Prabowo (LP2M IAIN Palopo, 2026)
Productivity The workload of members of the Criminal Investigation Unit (Satreskrim) of the Karawang Police is an important factor in supporting the successful implementation of police duties. Based on the results of the pre-survey, problems related to workload and work motivation were still found that affect the work productivity of members. This study aims to determine respondents' responses regarding workload and work motivation and to determine the work productivity of Satreskrim members based on the perceptions of direct superiors, and to analyze the influence of workload and work motivation on the work productivity of Satreskrim members. The research method used is a descriptive and associative method with a quantitative approach. The study population amounted to 62 people, consisting of 61 Satreskrim members as respondents for the workload and work motivation variables and 1 direct superior as the work productivity assessor. Data analysis was carried out using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and coefficient of determination with the help of the SPSS version 25 program. The results of the study indicate that partially workload has a positive effect on the work productivity of Satreskrim members. In addition, partially work motivation also has a positive effect on the work productivity of Satreskrim members . Workload and work motivation also influence the work productivity of Satreskrim members simultaneously. Based on the results of the study, it can be concluded that appropriate workload and very high work motivation contribute to the high work productivity of members of the Karawang Police Criminal Investigation Unit .